Role of health hazardous ethephone on nutritive values of selected pineapple, banana and tomato - Hakim, Md. Abdul; Obidul Huq, A. K.; Alam, Mahbub; Khatib, Alfi; Saha, B. K.; Formuzul Haque, K. M.; Sarker, Md. Zaidul Islam (WFL Publisher, 2012)
An experimental study of selected pineapple (Ananas sativus), banana (Musa acuminata) and tomato (Lycopersicon esculentum) was investigated on the basis of their biochemical and nutritional properties by the treatment of some doses of ethephone. It was found that the chemically treated samples ripened rapidly than untreated ones. The nutritional properties of chemically ripened fruits as well as market samples (ripe) were shown different from untreated. The chemically ripened samples showed shorter shelf life than non-treated samples. The highest vitamin C content of the selected non-treated fruits (17.5 mg/100 g in pineapple, 13 mg/100 g in banana and 20.2 mg/100 g tomato) and the lowest contentwas found in the market samples (10 mg/100 g in pineapple, 7 mg/100 g in banana and 12.3 mg/100 g tomato), whereas ethephone-treated groups contained the ascorbic acid 14.5 mg/100 g in pineapple, 9 mg/100 g in banana and 19.4 mg/100 g in tomato). Similarly the β-carotene content of ethephone-treated samples (63 μg/100 g in pineapple, 47 μg/100 g in banana and 757 μg/100 g in tomato) and market samples (31 μg/100 g in pineapple, 38 μg/100 g in banana and 512 μg/100 g in tomato) were less than that of control groups (78 μg/100 g in pineapple, 54 μg/100 g in banana and 807 μg/100 g in tomato). The mineral contents of samples in three groups showed ethephone-treated samples indicated less nutritional quality than untreated samples. Higher amount of lead and arsenic were found in all fruits and vegetables in both ethephone-treated and market samples but the concentrations were within acceptable limits.